2023
DOI: 10.30934/kusbed.1188587
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Listening to Music on Surgical Fear and Anxiety before Cardiac Surgery: A Randomized Clinical Trial

Abstract: Objective: Listening to music has been used as an intervention during both the treatment and rehabilitation process. Cardiac surgery is stressful and generates fear for most patients. This study assessed the effect of listening to music on the level of surgical fear and state anxiety of the patients, who were undergoing cardiac surgery. Methods: This randomized controlled trial consisted of 50 patients in the intervention group and 50 patients in the control group. Two days before cardiac surgery, the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Introduction to the OR environment by the RN circulator before surgery and providing information about intraoperative care can help reduce patients' anxiety levels. 26 In studies on surgical fear, music was found to reduce patients' surgical fear, 27 but therapeutic listening was not found to affect surgical fear. 28 Authors of another study emphasized that psychosocial interventions among breast cancer patients undergoing surgical procedures reduced their fear of the short-term outcomes of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction to the OR environment by the RN circulator before surgery and providing information about intraoperative care can help reduce patients' anxiety levels. 26 In studies on surgical fear, music was found to reduce patients' surgical fear, 27 but therapeutic listening was not found to affect surgical fear. 28 Authors of another study emphasized that psychosocial interventions among breast cancer patients undergoing surgical procedures reduced their fear of the short-term outcomes of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…29 In this study, we identified that surgical fear levels were relatively high compared to other study results, and that fear is experienced more in the preoperative period, similar to other the studies. 27,29 Patients' anxiety levels decrease with individual education, informative brochures, or audio materials during the preoperative period. 12 Nursing visits in the preoperative period that include multimedia could reduce perioperative anxiety.…”
Section: Discussionmentioning
confidence: 99%